An examination of strategy disclosure in the annual reports of South African listed companies - N. Padia; Y. Yasseen (South African Journal of Business Management, 2011)
This study examines the extent of strategy disclosure in the Annual Reports of South Africa's top one hundred companies listed on the Johannesburg Securities Exchange (JSE). Disclosure of strategy is voluntary and not required by law. Investigation into the strategy disclosure was carried out by scoring the amount of disclosure companies reported in their Annual Reports. Variables included items such as mission, goals and objectives. Two additional criteria, Human Immunodefiency Virus (HIV) / Acquired Immune Deficiency Syndrome (AIDS) and Black Economic Empowerment (BEE), were included specifically for the South African context.Results showed that maximum disclosure per criteria was low. Overall the scores of the variables indicate that although South African companies generally do disclose a lot more information on their strategy, only six per cent of companies made maximum disclosure on all twelve criteria. The lowest scores were obtained for HIV/AIDS and BEE. The low disclosure overall has implications for users of annual reports.
Keywords: 650